Fermentation of lactic acid to polylactic acid: a study - Abdullah, Nur Adilah (2017)
Polylactic acid (PLA) is one of the major commercially available polymers which widely used in the food packing materials, fibers, agricultural films and biomaterials. Synthesis of PLA from fermentative lactic acid is another new alternative substrate which it is contributes to the reduction of production cost, increase the renewable resources value, and development of bioplastic that is environmentally friendly materials. PLA was synthesis in a direct polycondensation method with suitable chosen catalyst which is ptoluenesulfonic acid (PTSA) to obtained higher molecular weight (Mw). The fermentative lactic acid was prepared from Lactobacillus rhamnosus TISTR 108 and used as a monomer of polymerization. The number average molecular weight (Mn) and molecular weight (Mw) of PLA products were analyzed by end-group analysis and High Performance Liquid Chromatography (HPLC). From the results, high molecular weight of PLA were obtained from commercial lactic acid by direct polycondensation under appropriate conditions which are 0.25 wt% PTSA as catalyst, temperature at 170°C and polymerizing time for 7 hr. The number average molecular weight (Mn) and molecular weight (Mw) of the PLA products in fermentative lactic acid were 2,627 and 232 Da, respectively, while for commercial lactic acid were 42,288 and 423 Da. From the research, it can be conclude that the best method for synthesis polylactic acid is by using direct polycondensation method.